2017
DOI: 10.5599/admet.5.3.423
|View full text |Cite
|
Sign up to set email alerts
|

ADME-Tox profiling of some water soluble chitosan derivatives

Abstract: Within this study we use a few computational tools for predicting absorption, distribution, metabolism, excretion and toxicity (ADME-Tox)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…To the best of our knowledge, this approach has never been conducted before. Similar studies have been performed for xenobiotics such as food supplements, steroids, food additives, and pesticides, revealing valuable results [30][31][32].…”
Section: K1 K2mentioning
confidence: 59%
“…To the best of our knowledge, this approach has never been conducted before. Similar studies have been performed for xenobiotics such as food supplements, steroids, food additives, and pesticides, revealing valuable results [30][31][32].…”
Section: K1 K2mentioning
confidence: 59%
“…The computational tools that are used in this study have been elaborated for assessing the pharmacological profiles and toxicological endpoints of new drugs, but they were successfully applied for other classes of chemicals: cosmetic ingredients and pesticides (Alves et al, 2018c; Roman et al, 2018a; Gridan et al, 2019), synthetic steroids found on the market as food supplements or veterinary drugs (Roman et al, 2018b), water soluble derivatives of chitosan (Isvoran et al, 2017). It illustrates their applicability for predicting pharmacological properties and toxicological endpoints for many classes of compounds.…”
Section: Methodsmentioning
confidence: 99%
“…It also conducted to the development of various computational tools that can be used for hazard assessment. They are recognized by the Organization of Economic and Cooperation Development (OECD) [15] and European Food Safety Association [16] and are constantly used nowadays in assessing the toxicological effects of various chemicals on humans [17][18][19][20][21]. Besides the large applicability of these tools for human hazard assessment, there are some limitations mostly related to the predictability of training models and to the fact that they do not take into account the dose.…”
Section: Introductionmentioning
confidence: 99%